(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
This paper is a second updated supplement to the host-parasite catalog of world Dryinidae published by Guglielmino & Olmi (1997, 2006). Forty one new records of relationships between Auchenorrhyncha and Dryinidae are listed, including thirty six new relationships discovered by the authors.